2009
DOI: 10.1557/jmr.2009.0058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nb doping on thermoelectric properties of Zn4Sb3 at high temperatures

Abstract: The thermoelectric properties of Nb-doped Zn4Sb3 compounds, (Zn1–xNbx)4Sb3 (x = 0, 0.005, and 0.01), were investigated at temperatures ranging from 300 to 685 K. The results showed that by substituting Zn with Nb, the thermal conductivities of all the Nb-doped compounds were lower than that of the pristine β-Zn4Sb3. Among the compounds studied, the lightly substituted (Zn0.995Nb0.005)4Sb3 compound exhibited the best thermoelectric performance due to the improvement in both its electrical resistivity and therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…A similar nonmonotonic behavior of the thermal conductivity with doping content was also observed in In-doped (Zn 1 À x In x ) 4 Sb 3 [14], Nbdoped (Zn 1 À x Nb x ) 4 Sb 3 [19] and Te-doped Zn 4 Sb 3 À x Te x [21] compounds, indicating that this is not a specific phenomenon for Fe-doped Zn 4 Sb 3 , but a relatively universal phenomenon in Zn 4 Sb 3 upon doping. Tsutsui et al [14] and other researchers [19] believed that point defects and lattice distortion were introduced in the lattice because of the large mass difference between them, and the dependence of lattice thermal conductivity on the content of In and Nb was regarded as a solid solution effect. But, why the solid solution effect is the strongest (corresponding to the lowest thermal conductivity) at the lightly doped contents in Zn 4 Sb 3 [14,19,21] is still puzzling.…”
Section: The Thermal Conductivity and The Dimensionless Figure Of Meritsupporting
confidence: 66%
See 2 more Smart Citations
“…A similar nonmonotonic behavior of the thermal conductivity with doping content was also observed in In-doped (Zn 1 À x In x ) 4 Sb 3 [14], Nbdoped (Zn 1 À x Nb x ) 4 Sb 3 [19] and Te-doped Zn 4 Sb 3 À x Te x [21] compounds, indicating that this is not a specific phenomenon for Fe-doped Zn 4 Sb 3 , but a relatively universal phenomenon in Zn 4 Sb 3 upon doping. Tsutsui et al [14] and other researchers [19] believed that point defects and lattice distortion were introduced in the lattice because of the large mass difference between them, and the dependence of lattice thermal conductivity on the content of In and Nb was regarded as a solid solution effect. But, why the solid solution effect is the strongest (corresponding to the lowest thermal conductivity) at the lightly doped contents in Zn 4 Sb 3 [14,19,21] is still puzzling.…”
Section: The Thermal Conductivity and The Dimensionless Figure Of Meritsupporting
confidence: 66%
“…Tsutsui et al [14] and other researchers [19] believed that point defects and lattice distortion were introduced in the lattice because of the large mass difference between them, and the dependence of lattice thermal conductivity on the content of In and Nb was regarded as a solid solution effect. But, why the solid solution effect is the strongest (corresponding to the lowest thermal conductivity) at the lightly doped contents in Zn 4 Sb 3 [14,19,21] is still puzzling. Nevertheless, one cannot exclude other factors that can give rise to this non-monotonous behavior of the thermal conductivity of Zn 4 Sb 3 upon doping.…”
Section: The Thermal Conductivity and The Dimensionless Figure Of Meritmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal doping is a function way and has been widely studied to optimize the thermoelectric 2 performance of materials [9][10][11][12]. Titanium is a typical metal with high melting point and has been reported that the properties of materials, such as electrical conductivity and thermostability, can be enhanced after its doping [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, doping approach can be used to enhance the thermoelectric properties by reducing its thermal conductivity and adjusting its carrier concentration [18,19]. Recently, doping of Cd, In, Al, Hg, Mg, Nb, Cu, Te and Se [16,[20][21][22][23][24][25][26][27][28][29] in Zn 4 Sb 3 has been reported. These studies showed that when doping with Cd, In or Mg, the thermoelectric performance of Zn 4 Sb 3 was not improved obviously.…”
Section: Introductionmentioning
confidence: 99%